Revision of East Kalimantan Vocational Students to Global Work Culture: An Empirical Study for Strengthening Education and Employment Policies in East Kalimantan Province - Naila Faradila; Rizky Zakariyya Rasyad (Nusantara Innovation Journal, 2026)
Objective: This study examines the phenomenon of culture shock and work adaptation among vocational education students participating in international internships. Limited local employment opportunities and increasing labor market competition require vocational graduates to possess global work readiness. However, a gap remains between the demands of the international workplace and graduates’ preparedness, particularly in terms of soft skills such as intercultural communication, adaptation to different work cultures, and psychological readiness. This study aims to analyze students’ experiences of culture shock, identify factors influencing their work adaptation, and explore the implications for vocational education policy in East Kalimantan, Indonesia. Design/Methods/Approach: This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with five vocational education students purposively selected from a total of twelve participants in an international internship program. Data analysis was conducted to identify patterns of culture shock, adaptation challenges, and factors that support students’ adjustment within multicultural work environments. Findings: The findings reveal that students experienced culture shock during the initial stage of workplace placement, characterized by differences in work culture, faster work pace, technology-driven systems, service communication practices, and language barriers. Work adaptation was influenced by social support, individual motivation, workplace observation, and the utilization of technology. The results indicate that successful adaptation to the global workplace is determined not only by technical competencies but also by soft skills, particularly intercultural communication and psychological work readiness. Originality/Value: This study provides empirical insights into the culture shock experiences of vocational students undertaking international internships within the context of vocational education in East Kalimantan. It further highlights the critical role of soft-skill development in enhancing the quality and competitiveness of vocational human resources. Practical/Policy implication: The findings underscore the need to strengthen vocational education policies through the development of soft skills, psychological preparedness, and intercultural competencies in order to improve graduates’ competitiveness in the international labor market.